2021
DOI: 10.1186/s12911-021-01623-6
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of actionable radiology reports using bidirectional encoder representations from transformers

Abstract: Background It is essential for radiologists to communicate actionable findings to the referring clinicians reliably. Natural language processing (NLP) has been shown to help identify free-text radiology reports including actionable findings. However, the application of recent deep learning techniques to radiology reports, which can improve the detection performance, has not been thoroughly examined. Moreover, free-text that clinicians input in the ordering form (order information) has seldom be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
1
16
1
Order By: Relevance
“…It has often been reported that BERT exhibits high performance, even with clinical text [36][37][38][39]. This is also true for this study, in which a model combining BERT and Bi-LSTM using clinical text recorded in daily practice allowed for fall prediction with an accuracy equal to or higher than that of conventional risk assessment tools.…”
Section: Fall Prediction Model Performancesupporting
confidence: 66%
“…It has often been reported that BERT exhibits high performance, even with clinical text [36][37][38][39]. This is also true for this study, in which a model combining BERT and Bi-LSTM using clinical text recorded in daily practice allowed for fall prediction with an accuracy equal to or higher than that of conventional risk assessment tools.…”
Section: Fall Prediction Model Performancesupporting
confidence: 66%
“…Radiology reports are an essential component of big medical data. Previous studies have fully demonstrated the feasibility of extracting evidence from radiology reports to assist clinical diagnosis and prognosis and promote automatic communication between physicians, radiologists and patients[ 37 , 39 , 42 ].However, the full potential of NLP remains to be further discovered, whereas deep learning-based algorithms have nearly revolutionized the paradigm of medical imaging. Radiology reports are primarily intended to provide information to assist with diagnosis; this information must be interpreted by physicians before being transmitted to patients.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zhang et al [ 41 ] designed and evaluated the feasibility of using pre-training models to extract key information from Chinese radiology reports fort lung cancer staging, the model achieved an F1 of 85.96%,while our study achieved an F1 of 84.10%. More recently, Nakamura et al [ 39 ] applied BERT without IDPT to classify actionable Japanese radiology reports, and attempted to predict a positive/negative “actionable tag”, the results seem promising with highest AUC of 0.95. In comparison with previous studies on radiology report classification, the labeling methods applied in this study were more complex, which require both physicians’ clinical experience and priori anatomic knowledge of radiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While maintaining trust, DxR needs to leverage smartphone capabilities a la Apple or even Google to learn about how, when, where, and who uses report information [ 17 ]. It must learn what information is really understood, what is actually used for decisions and actions, and, in particular, what information is not used [ 18 , 19 ]. Unused information has negative value as it unnecessarily wastes time.…”
mentioning
confidence: 99%